Verdeamarelo/anta e antropofagia: narrativas da identidade nacional brasileira - Helaine Nolasco Queiroz (2010)
The objective of the investigation is an analysis of the national identity of two of the most important modernists` groups of Brazil: verdeamarelo/Anta and Antropofagia. They were predominantly active within the period of 1926 and 1929. In view of these groups influence on the historical and cultural memory of the country, a review of the canonical critics and historiography about these groups was undertaken by means of a comparative analysis. Verdeamarelo/Tapir and Antropofagia formulated concepts about aestetics, nation and national identity which have been researched. Mutual aspects as well as differences were found and discussed. Furthermore, texts have been analyzed which were produced by the participants of the two modernists groups and by other intellectuals who had leaned on the ideas of Verdeamarelo/Tapir and Antropofagia. Based on that, the pedagogical character of the modernist speech in the narratives of verdeamarelo/Tapir and Antropofagia was verified. Both groups worked on a definition of the people and their historical transformation depending on time and location. Their approach was focused on avoiding regional fragments and times being projected in different dimensions. Based on the fundamental elements of people, location and time, the modernists narratives defined what nationality means in terms of art and literature and, in the last instance, what it means to be Brazilian.